The Pediatric Temporal‐spatial Deviation Index: quantifying gait impairment for children with cerebral palsy. (17th June 2019) - Zhou, Joanne Y; Zhang, Kevin; Cahill‐Rowley, Katelyn; Lowe, Evan; Rose, Jessica
Abstract : Aim: To develop an easily‐administered metric to quantify gait impairment in children and to assess its use in children with cerebral palsy (CP). Method: The Pediatric Temporal‐spatial Deviation Index (TDI) was developed from gait data collected from 75 typically developing children (37 males, 38 females; mean age 9y 4mo; interquartile range [IQR] 8–10y) and 17 children diagnosed with spastic CP (nine males, eight females; mean age 9y 9mo; IQR 9–11y), in Gross Motor Function Classification System (GMFCS) levels I to III, aged 7 to 11 years. Children walked on a pressure‐sensitive mat. Children with CP also completed 3D gait analysis. The Kaiser‐Meyer‐Olkin test of sampling adequacy was used for temporal‐spatial feature selection. Principal components obtained from temporal‐spatial gait parameters quantified deviation from typically developing gait. Deviation was normalized to a Pediatric TDI score mean (standard deviation [SD]) of 100 (10). The Pediatric TDI for children with CP was compared to 3D motion capture‐based Gait Deviation Index (GDI). Results: The Pediatric TDI was significantly lower for children with CP compared to typically developing children ( p <0.001), correlated with average GDI ( r =0.610, p =0.009), and demonstrated sensitivity (0.78) and specificity (0.88) to gait function, assessed with GDI. Interpretation: The Pediatric TDI is an easily administered, revealing gait metric that can be used in children with CP in pediatric clinics and for research. Detection of gait abnormalities in the clinic can expedite diagnosis and treatment. What this paper adds: The Pediatric Temporal‐spatial Deviation Index (TDI) is a single‐score index of gait deviation, based on nine parameters. The Pediatric TDI was more revealing than single temporal‐spatial gait parameters. The Pediatric TDI is quick and simple to administer in the clinic. What this paper adds: The Pediatric Temporal‐spatial Deviation Index (TDI) is a single‐score index of gait deviation, based on nine parameters. The Pediatric TDI was more revealing than single temporal‐spatial gait parameters. The Pediatric TDI is quick and simple to administer in the clinic.